A study on the effect of the violation of communication expectations between military professors and cadets on class interest and engagement - Jeongyeol Lee (선진국방연구, 2023)
This study aimed to find a way to enhance the education quality of military academies by analyzing how expectancy violations of communication between professors and cadets influence cadets' interest and engagement in class. This study was conducted as follows. First, a literature review of instructor communication and expectancy violation theories was conducted. Next, the instructor communication factor was measured using several authorized measurement scales targeting the cadets at KAAY. Finally, a number of three-step hierarchical regression analyses were conducted to derive implications regarding the effect of cadets' communication experiences and expectancy violations on cadets' interest and engagement in class. The results of these analyses are as follows. First, the analysis on how professors' communication expectancy violations affect cadets' interest in class revealed that expectancy violations of nonverbal friendliness had negative effects on emotional interest. Second, the analysis on how professors' communication expectancy violations affected cadets' engagement in class revealed that expectancy violations of professionalism had negative effects on interactive engagement, expectancy violations of nonverbal friendliness had negative effects on emotional engagement, and expectancy violations of validation had negative effects on interactive engagement. Finally, an analysis on the difference in how professors' communication expectancy violations affect cadets' interest and engagement in class revealed that the real experience of instructor communication affects cadets’ interest and engagement in class more than expectancy violations.